Screening of catalysts and operating conditions for the high yield production of isosorbide from sorbitol dehydration - Muhammad Ridzuan, Kamaruzaman; Chin, S. Y. (IOP Publishing, 2020)
Isosorbide (ISB), one of the important sorbitol (SL) anhydrides, can be produced through sequential intra-molecular dehydration of sorbitol derived from renewable biomass resources. Its rigid structure has granted the ISB a wide application in the polymer industries. Conventionally, acidic catalyst in liquid phase was used in the SL dehydration process. This homogeneous catalysed reaction gave low ISB yield and required additional downstream processes for catalyst separation. In the present study, a few types of catalysts were screened for sorbitol dehydration at a mild condition. Amberlyst 36 outperformed the other catalysts and resulted the highest SL anhydride selectivity of 86%. The effects of nitrogen purging and catalyst pre-treatment to the reaction performance were also investigated. The purging system did not significantly affect the SL conversion and selectivity of the desired products. The used of dried Amberlyst 36 exhibited a positive impact by increasing the SL conversion and SL anhydride selectivity to 67% and 98% respectively.